Long-term activation of PKA in β-cells provides sustained improvement to glucose control, insulin sensitivity and body weight. Issue 5 (2nd September 2016) - Levine, Joshua A.; Kaihara, Kelly A.; Layden, Brian T.; Wicksteed, Barton
ABSTRACT: Type 2 diabetes is associated with obesity, insulin resistance and β-cell failure. Therapeutic aims are to reduce adiposity, improve insulin sensitivity and enhance β-cell function. However, it has been proposed that chronically increasing insulin release leads to β-cell exhaustion and failure. We previously developed mice to have increased activity of the cAMP-dependent protein kinase (PKA), specifically in β-cells (β-caPKA mice). β-caPKA mice have enhanced acute phase insulin release, which is the primary determinant of the efficacy of glucose clearance. Here these mice were used to determine the sustainability of enhanced insulin secretion, and to characterize peripheral effects of enhanced β-cell function. Increased PKA activity was induced by tamoxifen administration at 10 weeks of age. Male mice were aged to 12 months of age and female mice to 16 months. Glucose control in both male and female β-caPKA mice was significantly improved relative to littermate controls with ad libitum feeding, upon refeeding after fasting, and in glucose tolerance tests. In female mice insulin release was both greater and more rapid than in controls. Female mice were more insulin sensitive than controls. Male and female β-caPKA mice had lower body weights than controls. DEXA analysis of male mice revealed that this was due to reduced adiposity and not due to changes in lean body mass. This study indicates that targeting β-cells to enhance insulin release is sustainable, maintains insulin sensitivity and reduces body weight. These data identify β-cell PKA activity as a novel target for obesity therapies.